2020
DOI: 10.1063/5.0012468
|View full text |Cite
|
Sign up to set email alerts
|

Passive control of coaxial jet with supersonic primary jet and sonic secondary jet

Abstract: The mixing enhancement of a coaxial jet with a Mach 1.4 primary jet and sonic secondary jet, at different convective Mach numbers, is presented in this study. Rectangular tabs of aspect ratios (AR = h/w, where h and w are the tab height and width, respectively) 2.0 and 0.75 were employed to manipulate the primary and secondary jets, respectively. The primary jet (C0) and coaxial jet without control or manipulation (C1) are studied in order to decouple the effects of rectangular tabs on jet mixing. Four differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Various authors (Kwan and Ko, 1977;Srinivasarao et al, 2014a;Matsumoto, 1973) studied incompressible flow coaxial jets. Kwan and Ko (1977) studied incompressible coaxial jets and observed that the PCL increases in the presence of an outer jet as observed in compressible jets (Papamoschou, 1997;Srinivasarao et al, 2017;Srinivasarao et al, 2014b;Lovaraju and Rathakrishnan, 2011;Perumal et al, 2020;Papamoschou, 1997). They also classified the regions of coaxial jets, namely, the initial merging zone (IMZ) (Region 1), intermediate zone (IZ) (Region 2) and fully merged zone (FMZ) (Region 3) as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Various authors (Kwan and Ko, 1977;Srinivasarao et al, 2014a;Matsumoto, 1973) studied incompressible flow coaxial jets. Kwan and Ko (1977) studied incompressible coaxial jets and observed that the PCL increases in the presence of an outer jet as observed in compressible jets (Papamoschou, 1997;Srinivasarao et al, 2017;Srinivasarao et al, 2014b;Lovaraju and Rathakrishnan, 2011;Perumal et al, 2020;Papamoschou, 1997). They also classified the regions of coaxial jets, namely, the initial merging zone (IMZ) (Region 1), intermediate zone (IZ) (Region 2) and fully merged zone (FMZ) (Region 3) as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 86%
“…The lip thickness (separation distance between primary nozzle and secondary nozzle) value plays an important role in the evolution of a coaxial jet. By using a surrounding jet along with an inner jet, the convective Mach number reduces, thereby suppressing noise can be achieved (Perumal et al , 2020), (Bennett and Shankar, 2020), (Papamoschou, 2004), (Papamoschou, 1997). In applications of coaxial jets, such as fuel-air mixing in a scramjet combustion chamber and dual mode ramjet combustion chamber, rapid mixing of the primary jet and secondary jet additionally outer jet with the ambient atmosphere is required for better combustion efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they proposed that the tab geometry effect and streamwise vortices positioned up to the jet's centerline would increase mixing by around 80%. The ongoing discussion of retardation in core length was investigated by Arun kumar et al (2020), in which the primary tabs show better mixing enhancement than secondary tabs resembles like characteristics of noncircular jets.…”
Section: Introductionmentioning
confidence: 99%
“…At NPR4, PCL increases to 104.34%. Recently, Perumal et al (2020) conducted experiments on supersonic CFJ (Mach 2 primary nozzle) and found an increase in PCL by 43% to 57.5% for NPR2.5 to 6.0. In this case, the lip thickness was 3.2 mm and the bypass ratio was around 1.9 to 2.5 for various NPRs.…”
Section: Introductionmentioning
confidence: 99%